2015
DOI: 10.1088/0067-0049/217/1/12
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Physics of Narrow Line Regions in Active Galaxies. Ii. The Siding Spring Southern Seyfert Spectroscopic Snapshot Survey (S7)

Abstract: Here we describe the Siding Spring Southern Seyfert Spectroscopic Snapshot Survey (S7) and present results on 64 galaxies drawn from the first data release. The S7 uses the Wide Field Spectrograph mounted on the ANU 2.3 m telescope located at the Siding Spring Observatory to deliver an integral field of 38 × 25 arcsec at a spectral resolution of R = 7000 in the red (530-710 nm), and R = 3000 in the blue (340-560 nm). From these data cubes we have extracted the narrow-line region spectra from a 4 arcsec apertur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 114 publications
7
86
0
Order By: Relevance
“…The sample consists of 47 Sy2 nuclei compiled by Dors et al (2015) and 14 observed by Dopita et al (2015). All emission line intensities are reddening corrected.…”
Section: Agn Samplementioning
confidence: 99%
“…The sample consists of 47 Sy2 nuclei compiled by Dors et al (2015) and 14 observed by Dopita et al (2015). All emission line intensities are reddening corrected.…”
Section: Agn Samplementioning
confidence: 99%
“…Three-colour [O III]-Hα-[N II] images and nuclear spectral properties for the first 64 S7 sources are compiled in [9]. This information can be used as a reference for source selection from S7 galaxies.…”
Section: Overview Of S7 Resultsmentioning
confidence: 99%
“…S7 is a targeted survey based on optical integral field spectroscopy, providing data for the central regions of ∼ 140 nearby Seyfert galaxies on ∼ 100 pc scales resolution [7,8,9,10]. S7 is designed to probe the AGN NLR by means of emission-line diagnostics and kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…Perpendicular to this disc is an ionization cone with an opening angle of 110 deg that is excited by the central AGN, highlighted in Fig. 17 and described in Dopita et al (2015). The gas within this cone is highly ionized and extends to 15 kpc.…”
Section: A P P L I C At I O N To S a N D S A M Imentioning
confidence: 99%